L' évolution récente de Kanalaki, centre de services du Phanari (Département de Prévéza) - Péchoux, Pierre-Yves; Sivignon, Michel (The Greek Review of Social Research, 1990)
[Δε διατίθεται περίληψη / no abstract available]